Chaotic Vibrations of Closed Cylindrical Shells in a Temperature Field - A.V. Krysko; J. Awrejcewicz; E.S. Kuznetsova; V.A. Krysko (Shock and Vibration)
Complex vibrations of cylindrical shells embedded in a temperature field are studied, and the Bubnov-Galerkin method in higher approximations and in the Fourier representation is applied. Both lack and influence of temperature field on the shell dynamics are analyzed.